2021
DOI: 10.1002/jppr.1741
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, barriers and facilitators of hospital pharmacists conducting practice‐based research: a systematic review

Abstract: Introduction Practice‐based research is essential in enhancing medication knowledge, quality use of medicines, the scope of the pharmacy profession and improving patient outcomes. This systematic review aims to uncover the attitudes of hospital pharmacists towards practice‐based research and their perceptions of the barriers and facilitators to undertaking practice‐based research. Methods A systematic search of MEDLINE, Embase, International Pharmaceutical Abstracts and Cumulative Index to Nursing and Allied H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…This study also identified that nearly every paper (97%) published by a hospital pharmacy department occurred in collaboration with a university. These results seem consistent with a systematic review of nine studies that identified hospitals with a university affiliation as a critical factor that improved hospital pharmacy participation in research 16 . In particular, Perreault et al 18 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This study also identified that nearly every paper (97%) published by a hospital pharmacy department occurred in collaboration with a university. These results seem consistent with a systematic review of nine studies that identified hospitals with a university affiliation as a critical factor that improved hospital pharmacy participation in research 16 . In particular, Perreault et al 18 .…”
Section: Discussionsupporting
confidence: 86%
“…15 Dedicated research time, research training, and support from fellow pharmacists, employers, and line managers have all been identified as ways to improve pharmacists' involvement in research. 16 SHPA have also implemented multiple strategies to increase the publication rates of hospital pharmacists. This includes the introduction of the SHPA Australian Pharmacy Residency program in 2019, which includes a mandatory research project component and the recognition of Research as a SHPA Specialty Practice stream.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, organizations such as the Global Fund and Save the Children were viewed as facilitators, as these organizations have recognized pharmacists' roles and hired them for logistic management. Similar to this study, other studies have demonstrated that pharmacists' involvement in providing care is facilitated by self-motivation, support from fellow pharmacists and the healthcare team, easy access to patients, and organizational support [38,39,43,44]. Our study indicates that lack of the aforementioned facilitators in Nepali context poses a significant barrier to pharmacists' involvement in HIV care delivery.…”
Section: Plos Onesupporting
confidence: 84%